Zebrafish Nk-lysins: First insights about their cellular and functional diversification. Issue 1 (July 2015) - Pereiro, P.; Varela, M.; Diaz-Rosales, P.; Romero, A.; Dios, S.; Figueras, A.; Novoa, B.
Highlights Four Nk-lysin genes were characterized for the first time in zebrafish (Danio rerio). A different expression pattern was observed under different experiments/conditions. A certain cell specialization in the production of Nk-lysins could be proposed. Two Nk-lysins were significantly up-regulated after SVCV challenge.